Inflammatory activity and intensity of Helicobacter Pylori colonisation in non-erosive antral gastritis - Gürkan BAŞARAN; Şerife BAŞARAN; Ali MERT; Zeynep ALGÜN; Hakan ŞENTÜRK (Turkish Journal of Gastroenterology, 2019)
-